Impact of Ethinyl Estradiol to Human Telomerase Reverse Transcriptase Activity on Complete Hydatidiform Mole Culture - Nurseta, Tatit; Wijasa, Arsana; Sitompul, Barlian (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To prove the effect of ethinyl estradiol as an activator on human Telomerase Reverse Transcriptase (hTERT). Method: The experimental study was conducted in vitro by using culture of complete hydatidiform mole trophoblast cell. We exposed the culture to ethinyl estradiol in varied doses and measured the concentration of hTERT through RT-PCR quantitative. There were 40 specimens as control group and 20 specimens exposed to ethinyl estradiol in different doses (10, 20, 40 and 80 mcg) as experimental group. The activity of hTERT was measured by RT-PCR and the concentration of it was assessed by ELISA. We analyzed the variables using ANOVA, Turkey post hoc and Pearson correlation test. Result: In control group, the concentration of hTERT was not detected. Meanwhile, the concentration among different doses of ethynil estradiol (10, 20, 40, 80 mcg) was 113,117.5; 114,507.6; 102,193.9; 127.546.1 amoles/ml, respectively. Among experimental group, they were significantly different both using F test (ANOVA) (p=0.001) and Turkey post hoc test (p=0.005). The correlation among group was 0.84 which meant higher level of ethinyl estradiol was correlated with higher activity of hTERT. Conclusion: Ethinyl estradiol impacts to the increase of hTERT activity on complete hydatidiform mole cell culture. [Indones J Obstet Gynecol 2016; 4-2: 93-96] Keywords: complete hydatidiform mole, ethinyl estradiol, human Telomerase Reverse Transcriptase (hTERT)